Food, Conservation, and Energy Act of 2008: Conservation Reserve Program (CRP) - Hicks, Erin, author; Seidl, Andrew, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2008)
The Conservation Reserve Program (CRP), enacted in 1985, provides payments to farmers to take highly erodible or environmentally sensitive cropland out of production for ten years or more to conserve soil and water resources. It is the federal government's largest private land retirement program. The program is administered by the Farm Service Agency of the U.S. Department of Agriculture (USDA), with technical assistance provided by USDA's Natural Resources Conservation Service. CRP has several subprograms, the best-known of which is the Conservation Reserve Enhancement Program (CREP). Congress reauthorized and amended the CRP through FY2007 in the 2002 farm bill and increased the CRP enrollment cap from 36.4 million acres to 39.2 million acres. Congress also added wildlife resources as a CRP objective and allowed participants to extend certain contracts up to 15 years. Along with a "general sign-up" in 2004 for landowners to submit bids to enroll acreage, USDA also announced two CRP initiatives: one to enroll 250,000 acres of bobwhite quail habitat and a second to enroll 250,000 acres of non-floodplain wetlands. Landowners may apply to enroll in these initiatives any time through December 31, 2007, or until the enrollment caps are reached. Between 2007 and 2010, 28 million acres under CRP contracts will expire, with 16 million acres in 2007 alone. In June 2006, USDA announced that contracts for approximately 13 million acres were renewed. An additional 1 million acres were also added under the latest general sign-up. Reenrollments for contracts expiring 2008-2010 were announced in late summer 2006.
Conservation Reserve Program (CRP)
October 2008 Agricultural and resource policy report, no. 1
October 2008.
Keywords: Conservation Reserve Program (U.S.); Land use, Rural -- United States; Rural development -- Law and legislation -- United States; Contracts, Agricultural -- United States; Agricultural conservation -- United States; Natural resources -- Law and legislation -- United States; Agricultural laws and legislation -- United States; Agricultural subsidies -- Law and legislation -- United States; Incentives in conservation of natural resources -- United States